HUBUNGAN PANCASILA DENGAN TEORI POSITIVISME DALAM PERSPEKTIF KONSTITUSI: The Relationship between Pancasila and Positivism Theory in a Conceptual Perspective - Mardika Mardika (Constitution Journal, 2024)
The origins of Pancasila as a basic norm (grundnorm) or staatsfundamentalnorm, as well as the 1945 Constitution of the Republic of Indonesia as the highest law in the hierarchy of laws and regulations in Indonesia can be traced through the development of positivist theories. The research seeks to test the relevance of positivist theories to the premise “Pancasila is the source of all sources of law.” The research methods used are a statutory approach, a conceptual approach and a doctrinal approach. The results of the research concluded that Pancasila in the 1945 Constitution of the Republic of Indonesia is a basic norm, which goes beyond the status of positive law and is placed outside the circle of positive legal order/hierarchy of statutory regulations, so its validity is much higher and is “mandatory” in nature rather than anything else, so that basic norms become the validity /touchstone for all positive law in Indonesia. Abstrak Asal mula Pancasila sebagai norma dasar (grundnorm) atau staatfundamentalnorm, serta Konstitusi UUD NRI 1945 sebagai hukum tertinggi dalam hierarki peraturan perundang-undangan di Indonesia dapat ditelusuri melalui perkembangan pemikiran teori-teori positivisme. Pada penelitian ini berupaya untuk menguji relevansi teori-teori positivisme terhadap premis “Pancasila adalah sumber dari segala sumber hukum.” Metode penelitian yang digunakan adalah pendekatan perundang-undangan, pendekatan konseptual dan pendekatan doktrinal. Hasil penelitian disimpulkan bahwa Pancasila dalam Konstitusi UUD NRI 1945 adalah norma dasar, yang melampaui status hukum positif dan diletakkan di luar dari lingkaran tata hukum positif/hierarki peraturan perundang-undangan, maka daya berlakunya jauh lebih tinggi yang sifatnya “wajib” daripada apapun itu, sehingga norma dasar menjadi validitas/batu uji bagi seluruh hukum positif di Indonesia.